(3ef GdChQLhGj dSjGJd hMJi GdOhMIs - (3YHO GdeWdH(B, (3YHO GdMejOs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2002)
(3GdLGJ GdfTCI hGdCgOGa, eHGOF hLhdGJ GdeaGhVGJ(B- (3CHYGO LhdI GdChQLhGj hfJGFLgG(B- (3GJaGbjI JMQjQ JLGQI GdNOeGJ (BGAT (3hCKGQgG(B- (3fTCI efXeI GdJLGQI GdYGdejI hgjcdgG GdJfXjej(B- (3CdjGJ efXeI GdJLGQI GdYGdejI(B- (3GdefGRYGJ GdJLGQjI hGdbVGjG GdeWQhMI(B- (3CdjI GdJYGed eY bVGjG GdEZQGb(B- (3GdeDJeQGJ GdhRGQjI defXeI GdJLGQI GdYGdejI hfJGFLgG(B- (3eSJbHd efXeI GdJLGQI GdYGdejI(B- (3eDJeQ GdOhMI hGdJhLgGJ GdeSJbHdjI defXeI GdJLGQI GdYGdejIs
Keywords: (3GdJLGQI GdNGQLjIs; (3efXeI GdJLGQI GdYGdejIs